2003
DOI: 10.1021/ac034387a
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Sputtering Yields Due to C60 versus Ga Bombardment of Ag{111} As Explored by Molecular Dynamics Simulations

Abstract: The mechanism of enhanced desorption initiated by 15-keV C60 cluster ion bombardment of a Ag single crystal surface is examined using molecular dynamics computer simulations. The size of the model microcrystallite of 165,000 atoms and the sophistication of the interaction potential function yields data that should be directly comparable with experiment. The C60 model was chosen since this source is now being used in secondary ion mass spectrometry experiments in many laboratories. The results show that a crate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
216
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 190 publications
(222 citation statements)
references
References 39 publications
6
216
0
Order By: Relevance
“…This is particularly true for the impact energy dependence observed under C 60 bombardment, where the experiment detects almost identical°ratios°as°predicted°from°the°simulations° [22]. Comparing the absolute yield values, we find the experimental C 60 data to be about a factor of 3 lower than predicted, whereas the value measured for Ga is almost exactly reproduced by the simulation.…”
Section: Total Yieldsupporting
confidence: 54%
See 3 more Smart Citations
“…This is particularly true for the impact energy dependence observed under C 60 bombardment, where the experiment detects almost identical°ratios°as°predicted°from°the°simulations° [22]. Comparing the absolute yield values, we find the experimental C 60 data to be about a factor of 3 lower than predicted, whereas the value measured for Ga is almost exactly reproduced by the simulation.…”
Section: Total Yieldsupporting
confidence: 54%
“…More specifically, the respective peaks in the TOF mass spectra are integrated over the entire isotopic abundance pattern, normalized to the primary ion current, and the ratio between the data obtained from C 60 ϩ and Ga ϩ bombardment is calculated as an enhancement°factor.°The°results°are°listed°in°Table°2°for 10, 15, and 20 keV impact energy. For comparison, the respective°data°obtained°from°the°MD°simulations° [22] are also presented. As can be seen from the table, we find a qualitative agreement between the measured data and the prediction from the simulations.…”
Section: Partial Yieldsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that these enhanced yields are produced with a concomitant increase in surface damage, but the yield enhancement surpasses that of damage [32]. Many studies have combined to develop the now accepted idea that the lower penetration depth and overlapping collision cascades of the polyatomic primary ion deposit more energy in the surface region, thus leading to increased sputtering [33][34][35][36][37][38][39].…”
mentioning
confidence: 99%